2010
DOI: 10.4317/jced.2.e82
|View full text |Cite
|
Sign up to set email alerts
|

Verruciform xanthoma located in anterior gingiva

Abstract: Verruciform xanthoma (VX) is a relatively rare benign lesion and oral predominantly, which occasionally affects skin and genital mucosa. It appears as a papule or single plaque showing a verrucous or papillomatous aspect, with variable color from reddish pink to gray. In majority of oral cases, it affects gingiva and alveolar mucosa such a solitary lesion. Histopathological findings are foamy histiocytes within elongated dermal papillae. Treatment consists of conservative excision surgery and recurrence is rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…7 Based on light and electron microscopic studies, Zegarelli et al proposed that foam cells are lipid-laden macrophages and oral VX may develop as a consequence of epithelial entrapment with subsequent degeneration and lipid accumulation. 8 They suggested a local irritant as the initiator of the disease process, because oral VX is frequently found on masticatory mucosa where localized trauma is very common. The predominant cells in the inflammatory infiltrate were T cells (51.8 ± 2%), and (43.3 ± 2)% were positive for human leukocyte antigen DR antigens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Based on light and electron microscopic studies, Zegarelli et al proposed that foam cells are lipid-laden macrophages and oral VX may develop as a consequence of epithelial entrapment with subsequent degeneration and lipid accumulation. 8 They suggested a local irritant as the initiator of the disease process, because oral VX is frequently found on masticatory mucosa where localized trauma is very common. The predominant cells in the inflammatory infiltrate were T cells (51.8 ± 2%), and (43.3 ± 2)% were positive for human leukocyte antigen DR antigens.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that an immune response may play a role in VX pathogenesis. 7,8 Zegarelli et al introduced the concept that the cause of accumulation of lipid-containing macrophages is epithelial degeneration. The products of epithelial breakdown elicit an inflammatory response which is manifested by a predominant neutrophil infiltrate in the epithelium and a subsequent release of lipid material through the epithelium which finally is scavenged by the macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…It is asymptomatic, has a low growth rate, and evolves to sizes varying from 0.2 to 2 cm. [5] There is no gender predilection and most commonly occurs in middle-aged persons with mean age of 40–50 years. [6] It can occur in any site but has a predilection for masticatory mucosa (gingival and hard palate).…”
Section: Discussionmentioning
confidence: 99%
“…The most characteristic feature is the presence of numerous foam or xanthomatous cells within lamina propria or connective tissue papillae. [5]…”
Section: Discussionmentioning
confidence: 99%
“…The salient histopathological feature is the abundance of foam cells (xanthoma cells) along with macrophages present in the soft papillary tissue. 1 The exact etiopathogenesis is still unknown, but the causative agents can be local factors like viral infections or trauma that have been suggested by hypothesis. Therefore this case report aims to present a case of verruciform xanthoma located in the marginal gingiva (lingual aspect) and describe the clinical features and histopathological aspects.…”
mentioning
confidence: 99%